Paul's Remediation. - Desilets, Sean (Journal of Religion, 2024)
This article explores how Jacques Derrida's claim that Christianity is an originally mediatized religion might inflect the concept of "messianic time" as derived from Paul's letters by Giorgio Agamben. Agamben's messianic time is the time it takes to conceive and represent time's own end. I argue that the self-consciously medial nature of Paul's letters allows us to see that this representation of telos is a collective experience. Three themes in Paul's letters to the Corinthians—his references to his body, his concern about his followers' visibility in cities, and his requests for money—demonstrate that Paul's theology is fundamentally a theology of media.